2014
DOI: 10.3126/av.v3i1.9981
|View full text |Cite
|
Sign up to set email alerts
|

Goal, Strategies and Programme of Safe Motherhood in Nepal

Abstract: The safe motherhood programme is one of the priority programme of Nepal. Its primary goal is to reduce maternal and neonatal mortality. Safe pregnancy, safe delivery and safe birth of new born are the major components of safe motherhood. This can be accomplished through increased access to effective antenatal, delivery and postnatal care and a massive health awareness activity in local communities.Academic Voices, Vol. 3, No. 1, 2013, Pages 19-23 DOI: http://dx.doi.org/10.3126/av.v3i1.9981

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Such efforts are aimed at reducing barriers on the demand side as well as on the supply side to ensure proper service provision, delivery and utilization. The National Safe Motherhood Program in 1997 [ 4 ], the National Safe Motherhood Plan 2002–2017 [ 5 ], the SBA policy in 2006 [ 6 ], the National Neonatal Health Strategy 2004 [ 7 ], and the Community Based Newborn Care Program in 2007 are some of the major programs, plans and policies to be highlighted. Notwithstanding these improvements, equity gaps in maternal and neonatal service utilization across geography, ethnicity and economic status have always been existing and is clearly evident from the findings of the Nepal Demographic Health Surveys of 2006, 2011 and 2016 [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts are aimed at reducing barriers on the demand side as well as on the supply side to ensure proper service provision, delivery and utilization. The National Safe Motherhood Program in 1997 [ 4 ], the National Safe Motherhood Plan 2002–2017 [ 5 ], the SBA policy in 2006 [ 6 ], the National Neonatal Health Strategy 2004 [ 7 ], and the Community Based Newborn Care Program in 2007 are some of the major programs, plans and policies to be highlighted. Notwithstanding these improvements, equity gaps in maternal and neonatal service utilization across geography, ethnicity and economic status have always been existing and is clearly evident from the findings of the Nepal Demographic Health Surveys of 2006, 2011 and 2016 [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased access to antenatal care, provision of skilled birth attendants and pregnancy care awareness programs at local level contributes to safer pregnancies and childbirth [11]. Previous studies have concluded that delivery in a health care facility offers much needed emotional support to pregnant women [47].…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal care uptake in rural settings is dependent on social and cultural factors [10]. Increased access to antenatal care, provision of skilled birth attendants and pregnancy care awareness programs at the local level contribute to safer pregnancies and childbirth [11]. In rural families, money, food and other logistics have all been seen to have an important influence on maternal health outcomes [12].…”
Section: Introductionmentioning
confidence: 99%